Model Construction and Dominant Mechanism Analysis of Li-Ion Batteries under Periodic Excitation - Zhihao Wang; Xingzhen Zhou; Bingxiang Sun; Weige Zhang; Xiaojia Su; Jinkai Shi; Qinhe Huang (Space: Science & Technology)
This study establishes for the first time a P2D-coupled non-ideal double-layer capacitor model (P2D-CNIC), which can be used for mechanism analysis under high-frequency periodic signal excitation. The novelty of this work is the consideration of the generally neglected electric double-layer capacitance and its dispersion effects, especially the capacitance of the solid electrolyte interface (SEI) film. The dispersion effect of the model is verified by a periodic current excitation signal and the corresponding phase change in the voltage response. Under sinusoidal alternating current (AC) excitation, a comparative analysis was conducted between the traditional P2D model, the traditional P2D model coupled with the ideal double-layer capacitor (P2D-CIC), and the proposed P2D-CNIC mechanism model. Furthermore, three models were evaluated under periodic short-circuit pulse discharge conditions to verify the accuracy and reliability of P2D-CNIC. The simulation results are used to analyze the dominant order of faradaic and non-Faraday processes under sinusoidal AC excitation, thereby providing insights into the internal mechanism analysis of lithium batteries under high-frequency cycling conditions.